2014
DOI: 10.1177/2327857914031000
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Interface Design for Knee and Hip Automatic Physiotherapy Assistant and Rehabilitation System

Abstract: In this paper, we report on a recent interface design and evaluation process for a new knee and hip automatic physiotherapy assistant and rehabilitation system (ARS). Interface design was concurrent with the development of ARS. The ARS has the potential to improve the automation of rehabilitation treatments, by providing quantitative measures of a patient’s motion. However, the complexity of rehabilitation information available to the therapist has increased with this additional information. We applied Ecologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…This is done by describing hierarchical means-ends relationships between process parameters. The approach has proven effective in shaping users' behaviors within system boundaries (i.e., a range of actions within which system goals are not violated) in a variety of application domains such as energy efficiency monitoring [13,14], maritime transport [9], aviation [4,8] and medical engineering [19,23]. In our previous work [40,41] we applied the WDA to the design of two VA interfaces which improved experts and novices' ability to understand complex situations in the domain of air traffic control.…”
Section: Related Workmentioning
confidence: 99%
“…This is done by describing hierarchical means-ends relationships between process parameters. The approach has proven effective in shaping users' behaviors within system boundaries (i.e., a range of actions within which system goals are not violated) in a variety of application domains such as energy efficiency monitoring [13,14], maritime transport [9], aviation [4,8] and medical engineering [19,23]. In our previous work [40,41] we applied the WDA to the design of two VA interfaces which improved experts and novices' ability to understand complex situations in the domain of air traffic control.…”
Section: Related Workmentioning
confidence: 99%
“…interfaces and also for resolving interface issues. In the context of EID, WDA has been performed to improve energy efficiency monitoring Jamieson, 2007, 2014), railway driving performance (Read et al, 2021), road (Baber et al, 2019) and maritime (Van Dam et al, 2006;Morineau et al, 2009;Fay et al, 2018) traffic management, medical engineering (Kwok and Burns, 2005;McEwen et al, 2012;Li et al, 2014), aviation (Amelink et al, 2005;Borst et al, 2007;Van Dam et al, 2008;Borst et al, 2008Borst et al, , 2010Ellerbroek et al, 2011Ellerbroek et al, , 2013 and in ATC (Lodder et al, 2011;Klomp et al, 2014;Mercado Velasco et al, 2015;Beernink et al, 2015;Borst et al, 2017;Ellejmi et al, 2018) In the context of resolving interface issues, Mumaw et al (2000a,b); Xu (2007) performed WDA and identified gaps and actions needed to resolve pilots' flight deck automation issues.…”
Section: Ecological Interface Designmentioning
confidence: 99%
“…By defining the constraints, the technique offers a way of understanding the rationale for operators' behaviour. The WDA technique has been used for the development of EID‐based interfaces in various applications, such as improving energy efficiency monitoring [HJ07, HJ14], railway driving performance [RBS∗21], road [BMM19] and maritime [VDMvP06, MBRT09, FSR18] traffic management, medical engineering [KB05, MFE12, LBK14], aviation [AMVPF05, BSMVP06, VDMVP08, BSM∗08, BMVP10, EVVD∗11, EBvPM13] and ATC [LCVPM11, KBMP14, MVBE∗15, BBE∗15, BBVPM17, EBP18]. Beyond interface design, WDA is widely used to systematically arrange large amounts of data enabling the analyst to effectively identify gaps and actions needed to resolve interface issues [MBG∗00, MSW∗00, Xu05].…”
Section: Related Workmentioning
confidence: 99%